1990
DOI: 10.18174/njas.v38i3b.16576
|View full text |Cite
|
Sign up to set email alerts
|

Feeding strategy during pregnancy for ewes with a large litter size. 1. Effect of quantity and composition of concentrates on intake and reproductive performance.

Abstract: In 6 trials, 40 Ile de France X Finnish Landrace ewes 2 to 8 years old were given during pregnancy diets containing 40% energy from concentrates and crude protein (CP) 196 or 91 g/kg or 60% energy from concentrates and CP 189 or 240 g/kg. Mean litter size was 3.26. The sum of the birth weights of lambs was affected by the treatment where a higher protein concentration was combined with a lower degradability of the protein. Net body weight gain was affected by litter size, ketosis and treatment. Metabolizable e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…These nutritional regimens, however, had no effect on the ewe live weight, BCS and back fat data at the end of the 14-day nutritional regimen period. The cause of this lack of difference is unknown, but may be a result of the decrease in rumen volume as previously reported in late pregnancy ( Forbes, 1968 ; Everts, 1990 ) thus reducing ewe intakes for both nutritional regimens. Kenyon et al (2013) , however, reported that triplet-bearing ewes, when offered similar pre- and post-grazing masses over the same time period to the present study, showed differences in ewe live weight, BCS and back fat depth.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…These nutritional regimens, however, had no effect on the ewe live weight, BCS and back fat data at the end of the 14-day nutritional regimen period. The cause of this lack of difference is unknown, but may be a result of the decrease in rumen volume as previously reported in late pregnancy ( Forbes, 1968 ; Everts, 1990 ) thus reducing ewe intakes for both nutritional regimens. Kenyon et al (2013) , however, reported that triplet-bearing ewes, when offered similar pre- and post-grazing masses over the same time period to the present study, showed differences in ewe live weight, BCS and back fat depth.…”
Section: Discussionmentioning
confidence: 83%
“…It can be postulated that in very late pregnancy twin bearing ewes may fail to physically consume sufficient herbage to meet their nutritional requirements ( Nicol and Brookes, 2007 ) when offered a ryegrass-white clover herbage due to rumen volume restriction as the conceptus increases in size ( Forbes, 1968 ). Further, Everts (1990) reported that multiple-bearing ewe intakes can actually be reduced in late pregnancy. Combined, these studies indicate that there may be little advantage in offering high levels of ryegrass-white clover herbage in late pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Morris and Kenyon (2004) suggested that in late pregnancy triplet-bearing ewes can fail to consume their theoretical requirements, even under unrestricted pasture conditions, due to ruminal space restriction. In support of this, Everts (1990a) reported that ewe intake in the last weeks of pregnancy actually decreased and that this was related to litter size. They suggested that this reduction in intake with larger litter sizes was potentially explained by; reduce abdomen space due to rapid uterine expansion, greater heat stress from more lambs in the uterus especially in ewes with an intact fleece, higher levels of oestrogen which has been shown to reduce intake, and a ewe in an energy deficit state is driven to energy mobilisation resulting in increased levels of free fatty acids which could result in reduced intake.…”
Section: Lamb Growthmentioning
confidence: 82%
“…Dry matter intake of ewes with an intact fleece is depressed during the last weeks of pregnancy on diets of roughage supplemented with concentrates. This intake is more severely depressed in ewes with a litter size of more than two lambs (Everts, 1990). The high energy demand and the limited intake capacity in ewes with a large litter size causes an energy deficit at the end of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…In the third and the fourth year the effect of a higher proportion of energy originating from concentrates at the end of pregnancy ( = treatment L60C) and in the fifth and sixth year the effect of a higher proportion of energy from concentrates combined with a higher protein supply and a lower protein degradability at the end of pregnancy (= treatment L60C + P) was studied. The characteristics of feed in take, incidence of acetonaemia and perinatal lamb mortality are reported in an earli er paper (Everts, 1990). The effects of the treatments on the pattern of some blood parameters (glucose, BHB and NEFA) were studied.…”
Section: Introductionmentioning
confidence: 99%